Reactivity of CO on Sulfur-Passivated Graphene-Supported Palladium Nanocluster Arrays - Düll, Fabian; Späth, Florian; Bachmann, Philipp; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2017)
Nanocluster arrays on graphene are suitable model systems for catalysis. We use this model system to study sulfur poisoning, which is a major deactivation process of heterogeneous catalysts. Using high-resolution X-ray photoelectron spectroscopy, we investigated the adsorption and desorption of CO on sulfur-poisoned graphene-supported palladium nanoparticles. We find that sulfur blocks CO adsorption sites, with hollow sites being most affected. From the unchanged desorption temperatures, we conclude that the Pd-CO bond strength is not altered by co-adsorbed sulfur. The degree of site blocking compared to the amount of sulfur indicates that the palladium nanoparticle surface is dominated by (111) and (100) facets.